Innovation and Industry Evolution - Reinganum, Jennifer F. (Quarterly Journal of Economics, 1985)
The theoretical literature on innovation has been concerned with a single innovation produced by a number of identical agents. By contrast, we consider a market in which one firm is the current incumbent, while the remaining firms are challengers. Moreover, we consider a sequence of innovations, so that success does not imply that the successful firm reaps monopoly profits forever after, but only until the next, better innovation is developed. We begin with a fully optimizing behavioral model and derive the equivalent of the Schumpeterian “process of creative destruction.” That is, a firm enjoys temporary monopoly power but is soon overthrown by a more inventive challenger. The essential point to grasp is that in dealing with capitalism we are dealing with an evolutionary process…The fundamental impulse that sets and keeps the capitalist engine in motion comes from the new consumers' goods, the new methods of production or transportation, the new markets, the new forms of industrial organization that capitalist enterprise creates [Schumpeter, 1942, pp. 82–83].